Analysis of Social Media Marketing and Brand Image on Purchase Intention for the 3Second Brand (Survey on Gen Z in Sukabumi City) - Akbar, Muhammad Fadilah; Ramdan, Asep Muhama; Nurmala, Resa (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the effect of Social Media Marketing and Brand Image on consumer Purchase Intention for the 3Second brand among Gen Z in Sukabumi City. Using a quantitative approach with a survey of 400 respondents and multiple linear regression analysis, the results show that Social Media Marketing and Brand Image have a positive and significant effect on Purchase Intention. The study highlights the importance of digital marketing strategies through social media and strengthening brand image to increase purchase intention, especially among digitally active Gen Z. These findings are expected to serve as a reference for developing local fashion marketing strategies.